Lead migration and fracture rate in dorsal root ganglion stimulation using anchoring and non‐anchoring techniques: A multicenter pooled data analysis. Issue 8 (17th July 2021) - Chapman, Kenneth B.; Mogilner, Alon Y.; Yang, Ajax H.; Yadav, Abhishek; Patel, Kiran V.; Lubenow, Timothy; van Helmond, Noud; Deer, Timothy; Kallewaard, Jan Willem
Abstract: Introduction: Dorsal root ganglion stimulation (DRG‐S) is a neuromodulation technique introduced in the last decade with evolving implant methods. Initial prospective research found low incidences of lead migration and lead fracture with DRG‐S. However, several recent studies have highlighted high lead migration and lead fracture rates with DRG‐S. We investigated the influence of lead anchoring on migrations and fractures. Methods: We performed a retrospective review between 2016 and 2020 of individuals implanted with DRG‐S leads by 4 experienced implanters. The implanters independently changed their standard practice regarding lead anchoring over time, with opposing trends (no anchoring > anchoring, anchoring > no anchoring). We compared lead migration and lead fracture rates between anchored and unanchored DRG‐S leads in the entire study cohort. Cox regression was performed on lead migration and fracture distributions. Results: We included 756 leads ( n = 565 anchored and n = 191 unanchored) from 249 patients. In unanchored leads, migration occurred in 16 leads (8.4%) from 13 patients (21.0%). In anchored leads, migration occurred in 8 leads (1.4%) from 5 patients (2.7%). Fracture in unanchored leads occurred in 6 leads (3.1%) from 6 patients (9.7%). Fractures in anchored leads occurred in 11 leads (1.9%) from 9 patients (4.8%). The migration survival distributions for the anchored and unanchored leads were statistically significantly different ( p < 0.01) with decreased survival for unanchored leads (hazard ratio = 5.8, 95% confidence interval [CI] = 2.2–15.5). Discussion: We found that anchoring DRG‐S leads significantly reduces lead migration when compared to leads placed without an anchor. There was no significant difference in fracture rate between anchored and unanchored leads.